Exclusive Breastfeeding Practices Among Postnatal Mothers: How Exclusive Are They? - Mohan P Joshi; Pushpa M Durge; Shams Khan; Samina M Ausvi (National Journal of Community Medicine, 2014)
Background – This study is designed to explore the breastfeeding practices among postnatal mothers and factors that determine exclusive breast feeding.